Comparison of Analysis Results pf pH, TSS, COD and Ammonia in Industry Wastewater with Sparing and SNI Methods - Dessy Nur Indryastuti; Ani Iryani; Muhammad Fathurrahman (Universitas Pakuan, 2022)
Sparing is a development of sensor technology to monitoring wastewater quality continuously and online, so it can be done in real time. Wastewater quality monitoring carried out in the laboratory using the SNI method still has several drawbacks, including large analysis costs, long analysis time and the use of chemicals that are not environmentally friendly. This study aims to determine the differences in the results of the analysis of the Sparing method with SNI on the parameters of pH, TSS, COD, and ammonia in the EWTP wastewater of PT